Identification Tree Damage on The Green line of The Mataram City - Ruhil Faizin; Andi Chairil Ichsan; Niechi Valentino (Jurnal Biologi Tropis, 2023)
Street Arya Banjar Getas – Dr. Sujono is one of the green open spaces in the form of lanes in Mataram City. Visually, trees along street Arya Banjar Getas– Dr. Sujono Mataram City experience disturbances in the growth phase caused by biotic and abiotic factors. This study aims to obtain information on the type and extent of tree damage in the Green Open Space area along street Arya Banjar Getas and Dr. Sujono in Mataram City. The method used in collecting primary data and secondary data on tree damage is by census or analyzing all trees in the two green lines of Mataram City. The number of vegetation species found on the green line is 19 with 832 individual trees. The 4 most dominant species found on the green line are Angsana (Pterocarpus indicus) with 244 individuals, Mahogany (Swietenia mahagoni) with 144 individuals, Flamboyan (Delonix regia) with 108 individuals and Canary (Canarium ovatum) with 101 individual trees. Based on the FHM (Forest Health Monitoring) book and using the parameters of tree damage values (Tree Level Index), 3 categories of damage to the green line were obtained, namely with a percentage of healthy class 91%, medium class 7%, and sick class 3%.